EFEK PAPARAN ALGINAT DALAM PANGAN TERHADAP KADAR PROTEIN TOTAL, ALBUMIN DAN GLOBULIN DARAH - Pramono Sasongko; Wahyu Mushollaeni (BUANA SAINS, 2017)
Clinical analysis to determined the toxicity of new material could be done by biochemical analysis of wistar rat blood serum such as blood protein, albumin, and globulin content. In case of decreasing of those biochemical analysis indicated the reduction of liver function in metabolism process. Hence, this study were conducted in order to determined toxicity effect of alginate presence extracted from brown seaweed Turbinaria sp.due to the blood protein, albumin, and globulin content of wistar rat blood serum. The study were conducted by Complete Randomized Design (CRD) with alginate concentration treatment which were 0.5%; 0.75%; 1%, and negative control. The results were shown that the treatment up to 1% of alginate concentration were not provide any toxicity effect in liver organ. These result was concluded due to the blood protein, albumin, and globulin content were presently still in a safe level.